2010
DOI: 10.1089/neu.2009.1171
|View full text |Cite
|
Sign up to set email alerts
|

Influence of PARP-1 Polymorphisms in Patients after Traumatic Brain Injury

Abstract: Poly(ADP-ribose) polymerase-1 (PARP-1) plays an important role in the cellular response to stress and DNA damage. However, excessive activity of PARP-1 exacerbates brain injury via NAD þ depletion and energy failure. The purpose of this study was to determine if tagging single nucleotide polymorphisms (tSNPs) covering multiple regions of the PARP-1 gene are related to outcome after traumatic brain injury (TBI) in humans. DNA from 191 adult patients with severe TBI was assayed for four tSNPs corresponding to ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 31 publications
2
24
0
Order By: Relevance
“…Evidence for sex-differences in PARP activation is also seen interrogating CSF from both adult and pediatric patients after severe TBI. Similar to the cerebral ischemia studies described above, PARP appears to have a greater role in males compared with females after brain injury [85][86]. Also consistent with the cerebral ischemia studies described above, and what appears to be the only major identified cell death pathway demonstrating female proclivity, release of cytochrome c into CSF (consistent but not pathognomonic of apoptosis) is higher in girls versus boys after severe TBI.…”
Section: Sex-based Disparity After Traumatic Brain In-jurysupporting
confidence: 76%
“…Evidence for sex-differences in PARP activation is also seen interrogating CSF from both adult and pediatric patients after severe TBI. Similar to the cerebral ischemia studies described above, PARP appears to have a greater role in males compared with females after brain injury [85][86]. Also consistent with the cerebral ischemia studies described above, and what appears to be the only major identified cell death pathway demonstrating female proclivity, release of cytochrome c into CSF (consistent but not pathognomonic of apoptosis) is higher in girls versus boys after severe TBI.…”
Section: Sex-based Disparity After Traumatic Brain In-jurysupporting
confidence: 76%
“…42). Furthermore, recent studies suggest that certain PARP polymorphisms may affect the outcome of various forms of critical illness (43,44). In summary, the field of PARP has entered the clinical stage, which underlines the timeliness of additional translational studies in various areas including burns and various forms or critical illness.…”
Section: Discussionmentioning
confidence: 99%
“…Clark and colleagues have investigated whether tagging single nucleotide polymorphisms (tSNPs) covering multiple regions of the PARP1 gene are related to outcome after TBI in humans (Sarnaik et al, 2010). DNA from 191 adult patients with severe TBI was assayed for four tSNPs corresponding to haplotype blocks spanning the PARP1 gene.…”
Section: Beyond Anticancer Therapy: Stroke Circulatory Shock Carmentioning
confidence: 99%
“…In multiple logistic regression analysis controlling for age, initial Glasgow Coma Scale score, and gender, the AA genotype of SNP rs3219119, which tags a haplotype block spanning the automodification and catalytic domains of the PARP 1 gene, was an independent predictor of favorable neurologic outcome. A second SNP (rs2271347), which tags a haplotype block spanning the automodification and catalytic domains of the PARP 1 gene, correlated with the amount of PARylated proteins in the cerebrospinal fluid, but did not correlate with the clinical outcome (Sarnaik et al, 2010). From these findings it can be concluded that after severe brain trauma in humans, a PARP1 polymorphism within the automodification-catalytic domain is associated with neurological outcome, while a polymorphism within the promoter region is associated with poly(ADP-ribose)-modified protein level.…”
Section: Beyond Anticancer Therapy: Stroke Circulatory Shock Carmentioning
confidence: 99%